LINGKUNGAN DAN MANAJEMEN PERUBAHAN DALAM ORGANISASI - SYAMSURIADI Syamsuriadi (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstract. Every organization in this modern era experiences challenges of change due to the uncertainty of the organization's environment. In the view of an open system, the organizational environment is described as everything that is around the organization that may influence and be influenced by the organization. Organizations cannot live without the environment, because both are inseparable entities. Thus changes in the environment must be followed by appropriate adjustment steps by the organization in order to maintain its effectiveness. One way to make adjustments appropriately is it requires management with planned management of change. A planned change process will be able to minimize the risks that will be caused. Whereas the unplanned process of change will have an adverse impact on the life of the organization. Therefore, in managing change it is necessary to apply various approaches, and change management models, so that organizations are able to lead strategic changes.